Taxonomie und Verbreitung der 'Kornmotten' (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1953)
Nomenclatural Actscochylidella Stainton, 1854 (Tinea), syn. n. pro Tinea ruricolella Stainton, 1849infimella Herrich-Schäffer, 1851 (Tinea), syn. n. pro Tinea cloacella Haworth, 1828secalella Zacher, 1938 (Tinea), syn. n. pro Tinea personella Pierce & Metcalfe, 1934